Editorial - Thomas, Joby (Atna Journal of Tourism Studies, 2007)
The second volume of Atna comes to you with our humble efforts to enrich tourism literature in India. We are delighted with the overwhelming response to the I volume from distinguished readers across India and abroad. Inspired by the constructive comments to the I volume, the second volume of Atna continue to incorporate articles on diverse areas of tourism such as sustainable tourism, heritage, medical tourism, cruises, cuisines, education, aviation etc. Raiesh N Ragde and Maduri T Sawant in their article on 'Proficiency of Foreign Languages : A study of the approved tourist guides of Aurangabad Region' state that, most of the tourist guides engaged in tourism business do not have proficiency of foreign languages, resulting in lack of appreciation of their role and responsibilities. Nedelea and Babu P George presents a case study of sustainable tourism development in Eastern Europe. This article points to the problems faced by hospitality and tourism industry in Romania and force the tourism sector to contemplate on the approaches towards sustainable tourism development. Strategies for sustainable eco-tourism by Maduri T Sawant examines the overall development of tourism and suggests strategies for sustainable tourism development. Sindhu Joseph critically analyses the potential and present stage of development of Bekal beach resort in Kerala in her article 'Special tourism Area- a critical study of Bekal.' 'Management of Eco-tourism sites: A case study of Aianta Ellora caves' by Raiesh N Ragde and Maduri Sawant highlights that the heritage contributes to the richness of any landscape and can attract innumerable tourists looking for cultural experiences in eco-friendly environment. Prospects of developing Medical tourism in India authored by Binoy T A draws attention to the pivotal role of medical tourism and calls for coordinated promotional strategies to develop medical tourism. Paramita Suklabaidya explores the potential of cruises as tourism product and the reasons for its growing popularity worldwide in her article 'New Age Tourism Product: The Cruise Industry - the Fastest growing Tourism Sector'. Gastronomy tourism can be a pull factor for many tourism market segments and the role of Gastronomy Tourism in promoting Jharkhand as a Tourist Destination is beautifully presented by Mohinder Chand, Ashish Dahiya and Lata S Patil. Issues of effective teaching and learning in tourism education by Toney K. Thomas reviews and evaluates the effectiveness of the application of skills in the industry. Joby Thomas and P. Pakkerappa in their article highlight the crucial role of HRD in airline industry to cope UP with the challenges of advancement in technology, changing market scenario, industry restructuring and more competitive business environment. To demonstrate the techniques of implementing intrapreneurship with examples from the tourism industry a case of Southwest Airlines of USA, is presented by Jyothirmoy Ghosh and Anianeya Swamy, and portrays how the intrapreneurship principles are applied effectively in tourism sector. On behalf of the editorial board I extend sincere gratitude to all the authors for contributing their scholarly articles to Atna. We look forward to the support, guidance and encouragement of academicians, researchers, professionals and well wishers of tourism and hospitality sector in our future endeavours. Joby Thomas Executive Editor